Physical activity promotion and obesity prevention in Girl Scouts: SNAP+ - Guagliano, Justin M.; Rosenkranz, Richard R. (My University, 2012)
Background: A previous version of Scouting Nutrition and Activity Program (SNAP) resulted in greater physical activity (PA) during troop meetings, but no impact on girls’ body mass index (BMI) or overall PA. The purpose of this study was to evaluate the effects of a six-month intervention that coupled the evidence-based program SNAP with a channel of communication to parents using health report cards (HRCs). Methods: Thirty-two Girl Scouts (mean age = 9.5, SD = 1.4 years) received the SNAP+ intervention. Girls were measured before and after the intervention on body composition, BMI, and 7-day step counts. Troop leaders were trained to implement an interactive obesity-prevention curriculum. Parents received health report cards designed to provide personalized information about their daughters’ PA and weight status. Results: The full sample of participants took more steps per day after the intervention (mean difference = 1,741, p = 0.007). Results showed that lower values for body fat percentage (p = 0.620), BMI percentile (p = 0.100) and BMI z-scores (p = 0.055) at intervention end were not statistically significant. In the subsample of girls at risk for overweight and obesity, there were lower values for BMI z-score (p = 0.010), BMI percentile (p = 0.027), and body fat percentage (p = 0.053). Conclusions: From this preliminary study, the SNAP+ intervention appears to be effective for Scout-based promotion of PA, and for the prevention of overweight and obesity in at-risk Girl Scouts, but further evaluation through a fully powered randomized controlled trial is warranted.
Physical activity promotion and obesity prevention in Girl Scouts: Scouting Nutrition and Activity Program+
Keywords: Physical activity; Obesity prevention; Health promotion; Girl Scouts; Intervention